PENGEMBANGAN KOMPETENSI PEDAGOGIK GURU ANAK GIFTED - Tri Sundari; Babang Robandi; Yuyus Suherman (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The purpose of this study is to find and formulate a pedagogical competency development program for gifted teachers suitable for use in Cugenang Gifted School at the elementary school level. In this study, the authors used qualitative, research methods used were qualitative with case studies. The research subject is the principal and class teachers, in qualitative research the main research instruments are the research itself, data collection techniques, namely interviews, observation, documentation studies, and data triangulation. The results of the study are the competencies of teachers of gifted children can be seen from the results of research on gifted teachers who actively support and diligently support actively in the classroom and can be seen in terms of speaking about the competencies of 10 teacher competencies and pedagogical competencies based on research results, we support that gifted teachers have maximally and special ideal with the needs of gifted children. Keywords: Gifted Children, Pedagogic Competencies, Qualitative